BOOK REVIEW OF ELEANOR AND PARK WRITTEN BY RAINBOW ROWELL - Azwari, Rendy (LANTERN (Journal on English Language, Culture and Literature), 2016)
Eleanor and Parkis a love story between Asian American boy and White American girl. Besides love story, it also deals with issues such as child abuse and bullying, which become interesting parts of the novel. Aside from reviewing the issues of child abuse and bullying, the writer also wants to discuss words that need extra references to understand them. Furthermore, the writer also wants to figure out the ending of this novel.